Increased DMT1 but not IREG1 or HFE mRNA following iron depletion therapy in hereditary haemochromatosis. Issue 8 (9th July 2004) - Kelleher, T; Ryan, E; Barrett, S; Sweeney, M; Byrnes, V; O'Keane, C; Crowe, J
Abstract : Background and aims: While upregulation of divalent metal transporter 1 (DMT1) and iron regulated gene 1 (IREG1) within duodenal enterocytes is reported in patients with hereditary haemochromatosis (HH), these findings are controversial. Furthermore, the effect of HFE, the gene mutated in HH, on expression of these molecules is unclear. This study examines duodenal expression of these three molecules in HH patients (prior to and following phlebotomy), in patients with iron deficiency (ID), and in controls. Methods: DMT1, IREG1, and HFE mRNA were measured in duodenal tissue of C282Y homozygous HH patients, in ID patients negative for the C282Y mutation with a serum ferritin concentration less than 20 μg/l, and in controls negative for C282Y and H63D mutations with normal iron indices, using real time polymerase chain reaction. Results: DMT1 and IREG1 mRNA levels were not significantly different in non-phlebotomised (untreated) HH patients compared with controls. DMT1 expression was significantly increased in HH patients who had undergone phlebotomy therapy (treated) and in patients with ID compared with controls. IREG1 was significantly increased in ID patients relative to controls, and while IREG1 expression was 1.8-fold greater in treated HH patients, this was not statistically significant. HFE mRNA expression was not significantly different in any of the groups investigated relative to controls. Conclusions: These findings demonstrate that untreated HH patients do not have increased duodenal DMT1 and IREG mRNA, but rather phlebotomy increases expression of these molecules, reflecting the effect of phlebotomy induced erythropoiesis. Finally, HFE appears to play a minor role in the regulation of iron absorption by the duodenal enterocyte.